Facility dogs as a tool for building rapport and credibility with child witnesses. (September 2020) - Spruin, Elizabeth; Dempster, Tammy; Mozova, Katarina
Abstract: The study examined the perspectives of legal professionals in relation to the use of facility dogs in building rapport and credibility with child witnesses. 70 legal professionals from across North America, who had experience interviewing children, both with and without the use of a facility dog, were recruited to take part. Utilising a holistic mixed-method design, data was collected via an online questionnaire, which asked participants about the impact they felt a facility dog had on rapport and witness credibility during police interviews with children. The results highlighted the positive impact that facility dogs have on child witnesses, not only in helping build rapport and witness credibility, but also for creating a more positive experience for young witnesses going through the criminal justice process. The results therefore provide evidence for the consideration of these dogs in countries beyond North America, as they provide an invaluable service to young witnesses.